Hubungan Pengetahuan Ibu tentang Keluarga Sadar Gizi dengan Status Gizi Anak Pra Sekolah - Erna Rahmawati; Anggraini Dyah Setiyarini (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Family knowledge especially mothers about nutrition awareness with nutritional status in pre-school children is very important to improve nutritional status. Pre-school children are at an age that is vulnerable to nutritional problems. This study aims to find the relationship between mothers' knowledge about nutrition-aware families and the nutritional status of pre-school children in Karangrejo Village, Tulungagung District. This type of research is a correlational study and based on time it is categorized as cross-sectional. The variables in this study were knowledge as the independent variable and the nutritional status of pre-school children as the dependent variable. The population of all mothers and pre-school children in Karangrejo village, Tulungagung district, was 106 respondents. Using accidental sampling, the results obtained were a sample size of 42 respondents. The statistical test used in this study was Spearman's rho. The study was conducted on 42 respondents with the results (45.2%) having less knowledge and (21.4%) less nutritional status of pre-school children. Analysis of the relationship between the two variables obtained a p value <α = 0.000 <0.05, meaning that h1 was accepted, meaning that there was a relationship between maternal knowledge about nutrition-aware families and the nutritional status of pre-school children in Karangrejo Village, Tulungagung District. There is a relationship between maternal knowledge and the nutritional status of pre-school children. school. Suggestions in this study are that it is expected to routinely carry out weight checks every month at school in order to monitor the growth and development of pre-school children so that if there is a nutritional disorder they can immediately get the right treatment.